2018
DOI: 10.4236/jct.2018.97048
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Obesity on Performing Lymphadenectomy and Its Outcome in Ovarian Cancer Patients

Abstract: Background: This study discusses the effect of obesity on the number of lymph nodes harvested during systematic LND and the LND-related complications in ovarian cancer patients. Methods: This retrospective study enrolled women with ovarian cancer who were consecutively subjected to open surgical resection that included systematic LND (pelvic and para-aortic) in the Oncology Center in Mansoura University (OCMU) during the period between January 2012 and June 2017. Patients were categorized according to the reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…It is hypothesized that operating on obese patients may cause worse surgical outcomes than operating on non-obese patients (5). But so far, accumulating studies have also been evaluating the effects of obesity on surgical outcomes in ovarian cancer, but the results have been inconsistent (4,(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Several studies indicated that obesity was associated with the surgical outcomes, such as optimal debulking status, postoperative complications, and return to operation room (7-11, 14, 15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is hypothesized that operating on obese patients may cause worse surgical outcomes than operating on non-obese patients (5). But so far, accumulating studies have also been evaluating the effects of obesity on surgical outcomes in ovarian cancer, but the results have been inconsistent (4,(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Several studies indicated that obesity was associated with the surgical outcomes, such as optimal debulking status, postoperative complications, and return to operation room (7-11, 14, 15).…”
Section: Introductionmentioning
confidence: 99%
“…But so far, accumulating studies have also been evaluating the effects of obesity on surgical outcomes in ovarian cancer, but the results have been inconsistent ( 4 , 6 – 16 ). Several studies indicated that obesity was associated with the surgical outcomes, such as optimal debulking status, postoperative complications, and return to operation room ( 7 11 , 14 , 15 ). But other studies did not suggest a possible link between obesity and these major surgical outcomes in ovarian cancer patients ( 4 , 6 , 13 , 16 ).…”
Section: Introductionmentioning
confidence: 99%